Where Can I Find a Library? Examining Access to Library Services in Asante Akyem North Municipality - Kwarteng Frimpong (SAGE Open, 2015)
The link between access to better libraries and students’ achievement has long been proven. But to residents in the Asante Akyem North Municipality, the benefits libraries offer remain illusory because of limited access. Using cross-sectional research design, the article examines staffing, collections, funding, library facilities, user perceptions, and the extent of utilization of the few libraries in the municipality. The author finds an indescribable deficit in the provision of library and information services, and attributes this primarily to an apparent lack of recognition of the important place libraries occupy in education delivery and knowledge acquisition.